2019
DOI: 10.1097/scs.0000000000005599
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics and Individual Differences of Palatal Rugae

Abstract: Purpose: This study aims to determine the number, symmetry, shape and individual characteristic of palatal rugae. Methods: In our study, we performed on subjects ages 16 to 57 (23.01 ± 7.12), ranging from a total of 230 (108 female and 122 male). Alginant impression material from each took dimensions of the upper jaw. Then casts were obtained by pouring hard casts. The shapes, lengths, and directions of rugae measured on these casts. The palatine photos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
1
4
2
Order By: Relevance
“…Upon further analysis of the right and left sides of palatal rugae, there was no statistical significance in the total number of rugae on either side with sinuous type being the dominant one. This aspect of the present result is congruent with Shetty KS et al, Wazir SS et al, Gezer R et al who discovered that there was no difference in the quantity of rugae between different races and palatal sides 21,22,23 . Similarly, Paliwal A et al, also supports this finding by exploring sinuous shape as a single configuration of rugae dominating on both sides of the palate 1 .…”
Section: Discussionsupporting
confidence: 92%
“…Upon further analysis of the right and left sides of palatal rugae, there was no statistical significance in the total number of rugae on either side with sinuous type being the dominant one. This aspect of the present result is congruent with Shetty KS et al, Wazir SS et al, Gezer R et al who discovered that there was no difference in the quantity of rugae between different races and palatal sides 21,22,23 . Similarly, Paliwal A et al, also supports this finding by exploring sinuous shape as a single configuration of rugae dominating on both sides of the palate 1 .…”
Section: Discussionsupporting
confidence: 92%
“…Secondary types did not differ between the age groups. The findings support but differ slightly from other studies reporting a significant difference between the age groups and the total number of rugae [ 20 ]. We found that the total number of fragmentary rugae was less in the older age groups.…”
Section: Discussioncontrasting
confidence: 79%
“…Only a few studies have looked into the influence of age on palatal rugae [ 18 - 20 ]. It was the purpose of this study to explore the patterns of palatal rugae in a Saudi population and to examine the differences based on age that could aid in identifying an individual.…”
Section: Introductionmentioning
confidence: 99%
“…This study group showed more backward directed rugae compared to forward and perpendicular rugae which is similar to the Bengali population (28). In contrast, forward directed rugae was predominant in Sudanese, Egyptians, Turkish, Gujarati, and Indians (22,27,(29)(30)(31)(32)(33). Generally, the population worldwide would show more forward directed rugae because there is a decrease in backward directed rugae with age.…”
Section: Discussionmentioning
confidence: 99%
“…The rugae were predominantly wavy which is commonly documented in most populations such as in Serbians, Turkish, Australians, Iraqi, Bosnians, Indians and Africans (20–26) and Chileans with sinuous patterns (13). In contrast, Egyptians and Indonesians had predominantly line rugae (3,27) alike Iranians and Koreans who have straight rugae patterns (16,19).…”
Section: Discussionmentioning
confidence: 99%